Sustainability in ecommerce: how can e-commerce start its sustainability journey? - Amirrudin, Faizatul Akmam; Mohd Shariff, Balqis (Universiti Teknologi MARA, Terengganu, 2022)
E-commerce can implement a number of sustainable practises as part of their new business strategy to appeal to the more ethical market. The following are some examples of sustainable practises that can be embraced by e-commerce players